2001
DOI: 10.1007/s002560100336
|View full text |Cite
|
Sign up to set email alerts
|

Mucoid degeneration of the anterior cruciate ligament mistaken for ligamentous tears

Abstract: Mucoid degeneration and an intact ACL can be suspected when an apparently thickened and ill-defined ligament with increased signal intensity on all sequences is identified in a patient with a clinically intact ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 9 publications
4
117
0
4
Order By: Relevance
“…Nevertheless, McIntyre et al [7] reported a retrospective analysis of MRI examinations in which six cases of mucoid degeneration were falsely interpreted as a tear of the ACL. In our case report, the radiologist also suggested a partial tear of the ACL, based on MRI findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, McIntyre et al [7] reported a retrospective analysis of MRI examinations in which six cases of mucoid degeneration were falsely interpreted as a tear of the ACL. In our case report, the radiologist also suggested a partial tear of the ACL, based on MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…McIntyre et al [7] found the lacking of synovial lining of the ACL during arthroscopy in 4 out of 10 cases of mucoid degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanations for increased T1-weighted and T2-weighted SI of native ACL include eosinophilic [37] or mucoid degeneration [38][39][40] similar to that seen in rotator cuff tendons [41]. ACL cystic degeneration and mucoid degeneration are both due to the mucinous degeneration of the connective tissue of the ligament, and they may also coexist [39,40].…”
Section: Discussionmentioning
confidence: 94%
“…(4) Finding of mucoid degeneration of the ACL on MRI showed well-defined ACL, showing intact fibres with intervening increased signal intensity lesion on all sequences, normal orientation of the ligament, and celery-stalk appearance. (5) His appearance can mimic acute or chronic interstitial partial tears of the ligament. (4) Anterior cruciate ligament mucoid degeneration is typically not associated with ligament instability and secondary signs of anterior cruciate ligament are absent.…”
Section: Discussionmentioning
confidence: 99%